2011
DOI: 10.1371/journal.pone.0026618
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Evolution of KCNQ4 in Echolocating Bats

Abstract: High-frequency hearing is required for echolocating bats to locate, range and identify objects, yet little is known about its molecular basis. The discovery of a high-frequency hearing-related gene, KCNQ4, provides an opportunity to address this question. Here, we obtain the coding regions of KCNQ4 from 15 species of bats, including echolocating bats that have higher frequency hearing and non-echolocating bats that have the same ability as most other species of mammals. The strongly supported protein-tree reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 33 publications
(52 reference statements)
2
38
1
Order By: Relevance
“…The evolution of echolocation and its associated high-frequency hearing makes laryngeal echolocating bats a fascinating mammal group for molecular evolutionary studies of hearing genes. Many genes associated with hearing have recently been proved to have undergone positive selection in echolocating bats and also in echolocating cetaceans [10], [11], [12], [13], [14], [15], [16], [70]. However, our results from the branch-site model A tests showed no significant evidence of positive selection in the major focal branches leading to echolocating bats, although one statistically supported positively selected site (260Q) was found in the ancestral branch of Yinpterochiroptera echolocating bats (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evolution of echolocation and its associated high-frequency hearing makes laryngeal echolocating bats a fascinating mammal group for molecular evolutionary studies of hearing genes. Many genes associated with hearing have recently been proved to have undergone positive selection in echolocating bats and also in echolocating cetaceans [10], [11], [12], [13], [14], [15], [16], [70]. However, our results from the branch-site model A tests showed no significant evidence of positive selection in the major focal branches leading to echolocating bats, although one statistically supported positively selected site (260Q) was found in the ancestral branch of Yinpterochiroptera echolocating bats (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Such excellent auditory performance making echolocating bats fascinating mammals for studying genes associated with hearing. Recently, many studies have revealed that some genes associated with hearing have undergone positive selection in echolocating bats and cetaceans [10], [11], [12], [13], [14], [15], [16]. Considering the important role of Myo6 in hearing, it is reasonable to hypothesize that the Myo6 may also be a target gene for positive selection in bats that use laryngeal echolocation compared with species that do not use laryngeal echolocation (the Old World fruit bats in the family Pteropodidae).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular evolution of Kcnq4 in bats shows several parallels with patterns seen in Prestin . Echolocating bats form a monophyletic group in the Kcnq4 nucleotide and amino acid sequence trees, and five amino acid sites are shared between echolocating bats in both suborders [Yinpterochiroptera and Yangochiroptera (Liu et al, 2011)]. Reconstruction of ancestral sequences suggests that bats in the two suborders evolved mutations at two amino acid sites in parallel.…”
Section: Echolocationmentioning
confidence: 99%
“…Ancestral reconstructions appeared to be reliable because both methods gave identical results, and nodal support values exceeded 99%. We then looked for parallel or convergent changes by comparing ancestral and extant protein sequences [6,8]. Parallel changes were required to have the same descendant amino acids from the same ancestral amino acids, and convergence was considered to have occurred when identical amino acids were derived from different ancestral amino acids.…”
Section: Materials and Methods (A) Species Pcr Amplification And Sequmentioning
confidence: 99%